The function f(x) is 3x+5
● (f-1)(x) = 3x+5 -1
● (f-1)(x) = 3x+4
Replace x with 3
● (f-1)(x) = 3×3+4 = 13
i don't know the explanation step by step
Next time please share ALL parts of the problem, including the possible answers.
Here all three terms are evenly divisible by 7, so we have:
7(4vw + 7v + 5w). It'd be OK to stop here.
We need the graphing tool.
Juan borrowed $10
His mother loaned him $3 more
= $10 + $3
He sold $25 worth of lemonade in the first week
If the pays his mother then the amount that will be left with him can be calculated as follows
= $25 - $13